Situation awareness and workload with the use of conflict resolution aid and vertical display - Yeo, Shirley Li Shan (2016)
Air Traffic Control (ATC) is a crucial service that ensures the safety and efficiency of aircraft flying from point to point in controlled airspace. It is thus vital that the right level and type of automation are integrated in all ATC providers to improve the Situation Awareness (SA) and reduce the workload of Air Traffic Controllers (ATCOs). Although existing studies have shown that reliable and interactive Conflict Resolution Aid (CRA) are beneficial in increasing SA of ATCOs and reducing workload levels in some cases, more empirical work needs to be done to examine the effects of different levels of reliability. In some studies, reliable and interactive CRA were found to reduce the workload of ATCOs while ensuring that they are kept in-the-loop through engaging them in strategy selection to resolve conflicts. In addition, the vertical profile display aid, designed to allow ATCOs to visualise the vertical trends of aircraft, will also be incorporated in this study. Hence this project aims to assess how SA and workload of ATCOs would be affected under two independent variables namely a “within-participant” variable which consists of the three different levels of reliability of the CRA and a “between-participant” variable which is the presence or absence of the vertical display aid. The participants were divided into 2 separate groups of 12. The first group would undergo the simulation with the vertical display aid while the second group would conduct the experiment without the vertical display aid. Each participant would be required to complete 3 different scenarios corresponding to reliable, unreliable and manual CRA. The results from this study revealed a higher SA as can be seen from a higher percentage of correct response recorded and a lower workload level from a lower percentage of timeout recorded under a reliable CRA with the presence of the vertical display aid. However, the presence of the vertical display aid was found to increase the question response latency under all 3 CRA conditions.